Bulbine decastroi (Asphodelaceae subfam. Asphodeloideae), a new peatland species with grass tuft-like rosettes from Mpumalanga, South Africa - Smith, Gideon F.; Grobler, Retief; Hankey, Andrew (Phytotaxa, 2023)
A new species of Bulbine, B. decastroi (Asphodelaceae subfam. Asphodeloideae), with grass tuft-like leaves, is described from north-central Mpumalanga province, South Africa. Bulbine decastroi is a substrate (peatland) specialist. The species is illustrated and compared to B. capitata.